The Influence of Prudence, Profit Growth, Corporate Governance on Quality of Profit - Ahmad Faris; Rosita Wulandari (Accounthink : Journal of Accounting and Finance, 2024)
This research aims to determine the influence of Prudence, Profit Growth, Corporate Governance on Quality of Profit in Energy Sector companies for the 2017-2022 period. Prudence variable with CNSV, Profit Growth is measured by the Profit Growth Index, Corporate Governance uses two proxies, namely Institutional Ownership and Managerial Ownership. Quantitative research and secondary data in the form of annual financial reports from the IDX and the official websites of each company. purposive sampling is the technique used in this research. This research has a sample of 9 companies. The Eviews version 12 software program is a data analysis tool in this research. The results of this research state that Prundence has a significant positive effect on Quality of profit, while Profit Growth and Corporate Governance have no effect on Quality of Profit.